2019
DOI: 10.1177/1178622119877837
|View full text |Cite
|
Sign up to set email alerts
|

Composted Municipal Green Waste Enhances Tree Success in Opencast Coal Land Reclamation in Wales

Abstract: The United Kingdom has a problem in the disposal of municipal green waste (MGW). This is unsuitable for landfill, but when properly composted may be beneficial to tree growth. A formal controlled trial of the 11-year growth (height, diameter at breast height [DBH]) and survival of 3 tree species was evaluated on degraded former opencast coal land on the margins of UNESCO’s Blaenavon Industrial Landscape World Heritage site in South East Wales. Forest reclamation is considered a viable cost-effective approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…e treatment of municipal green waste had growth rates comparable to untreated plants for mine site rehabilitation. e use of municipal green waste on degraded opencast coal land in South East Wales, the United Kingdom, had significantly greater survival rates, compared with trees planted without green waste [46]. Other studies have shown that the addition of compost not only increases soil fertility and plant biomass but also reduces the concentration of trace elements in plant species grown in metal-contaminated mine soils [47].…”
Section: Growth Of Fast-growing Tropical Treementioning
confidence: 98%
“…e treatment of municipal green waste had growth rates comparable to untreated plants for mine site rehabilitation. e use of municipal green waste on degraded opencast coal land in South East Wales, the United Kingdom, had significantly greater survival rates, compared with trees planted without green waste [46]. Other studies have shown that the addition of compost not only increases soil fertility and plant biomass but also reduces the concentration of trace elements in plant species grown in metal-contaminated mine soils [47].…”
Section: Growth Of Fast-growing Tropical Treementioning
confidence: 98%
“…In water-limited ecosystems, vegetation restoration is one of the options to prevent land degradation and soil erosion (Yu et al, 2016;Shi et al, 2019a). Ongoing vegetation restoration and climate change processes are having a far-reaching effect on soil carbon stocks, which creates an imbalance in carbon input/output ratios and results frequently in net releases back into the atmosphere (Haigh et al, 2019;Petrakis et al, 2020;van der Bank and Karsten, 2020). SOC is the most susceptible to changes in site conditions and is therefore the target of most evaluations (García-Díaz et al, 2016;Yeasmin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the yearly generated amount of combined organic waste (garden waste and other, compostable waste) was 103 kg per person [119]. The same data are 151.9 kg for Shiraz City [118] and 120 kg for England [120], which totals to 14.4 million tons per year for the UK [121]. The amount of MGW collected has a considerable variation over countries and within a country, locally, according to the location being urban or rural, and to local gardening practices and waste management traditions [119,120,122].…”
Section: Generation and General Composition Of Mgwmentioning
confidence: 99%
“…In Hungary, for example, less than half as much MW was incinerated, and less than one-eighth of MW ended up in landfills as was composted or recycled in 2019, when compared to figures of the late 1900s [128]. While dumping or landfill without any further use is still in practice, this practice raises environmental, social and financial concerns both in Europe (Wales) and in Southern America (Brazil) [121,129].…”
Section: Handling and Further Use Of Mgwmentioning
confidence: 99%